INNOVATIVE V-SHAPED CULTIVATING TINE - N. E. Rudenko; S. D. Kayvanov; F. N. Zavyalik (Сельскохозяйственные машины и технологии, 2016)
The main problem of soil secondary tillage is support of a tillage depth uniformity at the workingtools operation, fine-grained structure of a high layer and the smoothing without furrows and removal of the wet soil. The working tools allowing the machine to operate at the increased speeds are necessary, that will increasing its efficiency by 30-40 percent. The system of copying simplifying desingn and reducing variability of tillage depth requires the solution. The preseeding cultivators of the KPS-4 type are equipped with the 270-330 mm wide V-shaped tines and the 18 degrees crumbling angle. Tillage depth supported by the copying wheels. However, because they are distanced from working tools, it is impossible to achieve high uniformity of their course. Due to a crumbling angle and the shankes cutting a high layer the soil is opened out and wat layers remove up to the surface behind the shankes, that couses forrows formation. Their depth and width buildup with cultivator speed increase. The non-technological background for crops is created. The task is to exclude these negative phenomena by operation of the modern cultivators of the KPS-4 type. It can be solved due to mounting two-level V-shaped tines on the cultivator. The lower and upper ploughshares fixed on one shank. Both ploughshares are sharpened. They allow to refuse the copying wheels and to increase the cultivator operation speed to 16-18 km per hour. The upper ploughshare serves as the copying element. The tillage depth is stabilized because of the upper ploughshare as the copying element, and the lower ploughshare cutting weeds move in one plane. The tine point fixed over the upper ploughshare provides escape of the weeds cut with the upper ploughshare. It is promoted by its Moebius band surface. The innovative V-shaped tine executes technological process qualitatively. During field tests it is determined that the rate of soil crumbling reached 87-91 percent. If the technological effectiveness coefficient for ordinary tines is equal 0.4, then for offered it reaches 1.0. Application the spike-tooth harrow in the aggregate with a cultivator is excluded, the separate copying elements are not required that simplifies cultivator design significantly.